Marketable Branding In Political Marketing - Dewi Novianti; Retno Hendariningrum; Wahyuni Choiriyati (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2010)
The method used was the CDA (Critical Discourse Analysis) from the perspective of com- municative event. This research involved the analysis of the relationship between three dimensions: text, the practice of discourse (discourse practice, namely the process of production and consump- tion of text), and sociocultural practices (sociocultural practices, namely the level of society or culture). To dismantle the ideology behind the text, Van Dijk’s framing model was used. The results showed that candidates with high popularity did not necessarily marketable figure for the party. The result of this research confirms that the Brand that is sellable in a place may not be sellable else- where. It depends on who the customers (constituents) and what products to offer. Hence the logic of the market more effectively in the mechanism of political trading became a perspective in analysing celebrity politician phenomenon.